2018
DOI: 10.1111/jdi.12839
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age at menarche on obesity and glycemic control in Japanese patients with type 2 diabetes: Fukuoka Diabetes Registry

Abstract: Aims/IntroductionA younger age at menarche is associated with obesity and type 2 diabetes in adult life. The impact of early‐onset menarche on obesity and glycemic control in type 2 diabetes has not been investigated. The present study examined the relationship between age at menarche and obesity and glycemic control in type 2 diabetes.Materials and MethodsA total of 2,133 patients with type 2 diabetes aged ≥20 years were divided into groups according to age at menarche (≤11, 12, 13, 14 and ≥15 years). A retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
0
22
1
1
Order By: Relevance
“…Lee et al reported Women with age at menarche ≤12 years had signi cantly higher levels of triglycerides (β coe cient = 37.83, P = 0.02).Beside that hypertriglyceridemia was signi cantly increased at early menarche with 1.99 (95% CI: 1.16-3.41, P < 0 01) (1). Hozoori et al suggested Body mass index, waist circumference (WC), and Weight were inversely and signi cantly associated with the age of menarche (P<0.01) (49). Also Wronka was showed a signi cant relationship between weight and BMI with the age at menarche (50) Strengths and Limitations of the Study:…”
Section: Resultsmentioning
confidence: 84%
“…Lee et al reported Women with age at menarche ≤12 years had signi cantly higher levels of triglycerides (β coe cient = 37.83, P = 0.02).Beside that hypertriglyceridemia was signi cantly increased at early menarche with 1.99 (95% CI: 1.16-3.41, P < 0 01) (1). Hozoori et al suggested Body mass index, waist circumference (WC), and Weight were inversely and signi cantly associated with the age of menarche (P<0.01) (49). Also Wronka was showed a signi cant relationship between weight and BMI with the age at menarche (50) Strengths and Limitations of the Study:…”
Section: Resultsmentioning
confidence: 84%
“…In adolescence, body composition varies according to age, sexual maturation and physical growth, with physiological increase of adipose tissue, being higher in females, because this accumulation of body fat is essential for the beginning and maintenance of menstrual cycles and consequently for the reproductive process (2,31) . However, it should be considered that this is an age of many changes and therefore is a critical period for the development of obesity (32,33) .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The areas under the curve for BMI, WtHR, BAI and BRI were considered very good or excellent in adolescents in general, but, most of these values were lower compared to those analyzed by sex and period of adolescence. Assessing the accuracy of anthropometric indices to estimate body fat is necessary, especially in this age group and due to changes in body composition that occur during adolescence (2) . We suggest the use of specific cutoff points for the various adiposity indices, according to the adolescent's sex and age, in order to obtain a more accurate and reliable diagnosis of excess body fat.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The increasing trend of diabetes prevalence has coincided with the decline of age at menarche in China. 4,5 Accumulating evidence suggested that earlier age at menarche was associated with higher risk of obesity, 6 elevated levels of blood glucose, and insulin resistance. 7 However, studies on the association between age at menarche and the risk of diabetes were limited, and the findings were inconsistent.…”
Section: Introductionmentioning
confidence: 99%